UPAYA PENINGKATAN STRATA DESA DAN KELURAHAN SIAGA AKTIF DI KABUPATEN SIDOARJO - Ida Ernani (Poltekkes Kemenkes Surabaya, 2016)
The level of Active Alert Village is used as performance indicator of Community Health Center and description of public and government capability to achieve public independence in health which hasn’t fulfilled since Year 2012 until Year 2014. Organization Development (OD) is used to know how the factor can affect the Active Alert Village level. In this case Pokjanal and Forum Active Alert Village contribute to improved the level of Active Alert Village. This study aimed was to develop efforts to improve level of Active Alert village in Sidoarjo. With multistage random sampling technique obtained 144 Pokjanal and Forum Active Alert village members for the research samples. The result of research that all variabel, based on Paretto’s diagram 80/20, except partnership were problematic issue that should be solved. Furthermore, to see the influence of each problematic variabel, linear regression test is used with value of p 0,005. The result is: there was significant effect between, purpose, funding, the primary health care facility, the human resource with legal framework of Active Alert Village. There was significant effect between legal framework of Active Alert Village with social factors (Clean and Healthy Behavior, Pokjanal and Forum Active Allert Villages activity, Posyandu and other Health Effort Based on Community activity). There was a significant effect of social factors with result of Active Alert Village level; next there was significant effect between the funding and the human resource with the primary health care facility. There was significant effect between the primary health care and legal framework of Active Alert Village with stages of development of Active Alert Village (preparation stages, action stages, sustainability stages). There was a significant effect between the stages of development with social factors. There was a significant effect of social factors with result of Active Alert Village level; and last there was significant effect between the human resource with social factors. There was a significant effect of social factors with result of Active Alert Village level. Sidoarjo Health Officer as stakeholders on Active Alert Village follow up on these recomendations with a more appropriate intervention to improved Active Alert Village level based on the General Guidelines Handbook for Development of Villages Active Standby (Minister of Health of the Republic of Indonesia Number: 1529 / Menkes / SK / X / 2010). It is importance to improve the level of Active Alert Village by analyse on eight indicators stages of Active Alert Village as the way to achieve public health in villages. While for other researchers, this study can be used as material for futher research.Keywords: Solving community health problem in village, Developing Improvement effort of Active Alert Village level, Organization Development (OD).